Wage and salary administration - Zollitsch, Herbert G.; Langsner, Adolph (Cincinnati : South-Western Pub. Co., 1970)
This book is intended as a textbook for undergraduate and graduate college students. In addition, practitioners in industrial engineering and wage and salary administration, and others interested in gaining an insight into the various activities, principles, and techniques of compensation should find the book resourceful.
In first edition Langsner's name appeared first on the title page.
Includes index.
Includes bibliographical references: p. 759-765.
hza 12/07/2018
Loans
Keywords: Wages